The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/jb/mvu002
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-sensitive cellular transport

Abstract: The energy sensing AMP-activated protein kinase (AMPK) regulates cellular and whole-body energy balance through stimulating catabolic ATP-generating and suppressing anabolic ATP-consuming pathways thereby helping cells survive during energy depletion. The kinase has previously been reported to be either directly or indirectly involved in the regulation of several carriers, channels and pumps of high significance in cellular physiology. Thus AMPK provides a necessary link between cellular energy metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…It led to NF-κB separating from IκB and entering the nucleus, followed by initiating or enhancing the inflammatory genes transcription and promoting expression of inflammatory factors and inflammatory chemokines, such as tumor necrosis factor-α (TNF-α) and Interleukin-12 (IL-12) [35,36]. TAK1 also activated the mitogen-activated protein kinase (MAPK) signaling pathway, which led to the activation of subgroups extracellular signal-regulated kinase (ERK), p38 mitogen-activated protein kinase and C-jun n-terminal kinase (JNK), followed by formation of transcription factor activator protein-1 (AP-1), regulation of IL-1, IL-6 and TNF-α and other inflammatory factors of transcription in the end [37,38]. Consistent with the effects of Phellinus linteus polysaccharides on LPS-stimulated THP-1 cells [39], CSP-1 treatment significantly inhibited ROS generation and led to downregulation of MyD88 mRNA and TRAF-6 mRNA expression in LPS-induced THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It led to NF-κB separating from IκB and entering the nucleus, followed by initiating or enhancing the inflammatory genes transcription and promoting expression of inflammatory factors and inflammatory chemokines, such as tumor necrosis factor-α (TNF-α) and Interleukin-12 (IL-12) [35,36]. TAK1 also activated the mitogen-activated protein kinase (MAPK) signaling pathway, which led to the activation of subgroups extracellular signal-regulated kinase (ERK), p38 mitogen-activated protein kinase and C-jun n-terminal kinase (JNK), followed by formation of transcription factor activator protein-1 (AP-1), regulation of IL-1, IL-6 and TNF-α and other inflammatory factors of transcription in the end [37,38]. Consistent with the effects of Phellinus linteus polysaccharides on LPS-stimulated THP-1 cells [39], CSP-1 treatment significantly inhibited ROS generation and led to downregulation of MyD88 mRNA and TRAF-6 mRNA expression in LPS-induced THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…How AMPK regulates ion channels is diverse and tissue/cell type-specific (Andersen & Rasmussen 2012, Dermaku-Sopjani et al 2014). For example, constitutively active AMPK slows the inactivation of voltage-gated sodium channels (Na v 1.3) and shifts the voltage-activation curve toward more hyperpolarized potentials in rat ventricular myocytes (Light et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Ab production is regulated by the concentrations of glucose in the culture media. As AMPK serves as a metabolic sensor governing the downstream pathways to cope with energy crises (Burkewitz et al 2014;Dermaku-Sopjani et al 2014;Xiao et al 2011), we further examined the role of AMPK in Ab production. Using pharmaceutical agents to manipulate AMPK activities in APP cells grown in media containing different levels of glucose, we found that energy status and AMPK cooperatively affected the production of Ab.…”
Section: Discussionmentioning
confidence: 99%